Development of a high-yield reassortant influenza vaccine virus derived from the A/Anhui/1/2013 (H7N9) strain - Nakamura, Kazuya; Shirakura, Masayuki; Suzuki, Yasushi; Naito, Tadasuke; Fujisaki, Seiichiro; Tashiro, Masato; Nobusawa, Eri (Vaccine, 2016)
•We have developed a 6:2 reassortant vaccine virus for avian influenza A (H7N9).•The original virus stock, A/Anhui/1/2013 (H7N9), was a quasi-species.•A125T of NIIDRG-10.1 HA might enhance the growth ability of the virus. In April 2013, the first three fatal cases of human infection with an avian influenza A virus (H7N9) were reported in China. Because of a pandemic threat by this virus, we have commenced to develop candidate vaccine viruses (CVVs). Three 6:2 genetic reassortant viruses with different hemagglutinin (HA) sequences, NIIDRG-10, -10.1 and -10.2, were generated by a reverse genetics technique between the high egg-growth master virus, A/Puerto Rico/8/34 (H1N1) and A/Anhui/1/2013 (H7N9), kindly provided by the Chinese Center for Disease Control and Prevention. The different HA gene sequences of the three CVVs were derived from the original virus stock. NIIDRG-10 possesses HA, whose sequence is identical to that of the original A/Anhui/1/2013 (H7N9) in the Global Initiative on Sharing Avian Influenza Data (EPI439507), while NIIDRG-10.1 and -10.2 possess amino acid differences, A125T and N123D/N149D, respectively, compared with NIIDRG-10. NIIDRG-10 replicated in embryonated chicken eggs with low hemagglutination titer 128, whereas NIIDRG-10.1 and -10.2 grew well with hemagglutination titer 1024. These viruses reacted well with a ferret antiserum raised against the original A/Anhui/1/2013 virus. Ferret antiserum against NIIDRG-10.1 reacted well with A/Anhui/1/2013 similar to the homologous virus NIIDRG-10.1. These results indicated that NIIDRG-10.1 passed the two-way test of antigenic identity. In contrast, the ferret antiserum against NIIDRG-10.2 reacted with A/Anhui/1/2013 at an 8-fold lower hemagglutination inhibition titer than with the homologous virus NIIDRG-10.2, indicating an antigenic change. The total and HA protein yields of NIIDRG-10.1 were 14.7 and 6.9μg/ml, respectively, similar to those levels of high-yield seed viruses of seasonal influenza vaccines. NIIDRG-10.1 was approved as one of the CVVs for H7N9 viruses by the WHO in 2013. The candidate vaccine derived from NIIDRG-10.1 is currently being evaluated in a phase II clinical study in Japan.